OP108 Health Intervention Assessment Report Adaptation: Tunisian Experience. (12th January 2018) - Allouche, Wafa; Ouertatani, Hella; Jameleddine, Mouna; Grati, Hela; Jlassi, Khalil; Hammouda, Mohamed Ben; Attieh, Randa; Asua, José; Gutiérrez-Ibarluzea, Iñaki; Zghal, Khaled; Brahem, Asma Ben
Abstract : INTRODUCTION: Health Technology Assessment (HTA) reports adaptation process is an important tool for emerging HTA agencies. INASanté (National Instance for Accreditation in Healthcare) has chosen to rely on this approach, to develop its first health intervention assessment report: comparative study of computed tomographic colonography versus standard colonoscopy for colorectal cancer screening. METHODS: Following consultations with healthcare professionals, the PICO question related to the colorectal cancer screening issue in Tunisia was determined. A literature search strategy covering 10 years (2006-2016) was carried out. Several databases including HTA on the net were explored. Then two independent reviewers conducted literature screening and realized a PRISMA flow diagram. Full text selected reports were submitted to three critical appraisal tools: PRISMA checklist, INAHTA checklist and Critical Appraisal Tools (FLC 2.0). The EUnetHTA adaptation toolkit was used to determine reports adaptability by assessing relevance, reliability and transferability. A structured study of the Tunisian context based on a qualitative data analysis was elaborated. The data synthesis and reporting were finalized with the contribution of a working group. Then an external peer review was conducted before the report dissemination. RESULTS: Eighty reports were screened to finally retain four eligible. After a critical appraisal performed by two independent reviewers, two reports from the Canadian Agency for Drug and Technolgies in Healthcare and AETSA were selected to be assessed using the EUnetHTA adaptation toolkit. Regarding transferability criteria, the second report was retained. The context study has consisted in a qualitative analysis of seventeen individual interviews with healthcare professionals involved in colorectal cancer screening issues and an up to date Tunisian literature review. The final adapted report was a combination between relevant extracted data from AETSA report and synthesis of the Tunisian context analysis. CONCLUSIONS: This HTA report represents a tool for policy makers to establish the appropriate colorectal cancer screening program for the Tunisian context. HTA reports adaptation process is the best way to give evidence on emerging technologies without wasting time and resources.